PROPOSED BUDGET -- 1991 (Tufts Archival Research Center, 2007)
Confidential; Report from the Tobacco Institute's (TI) public affairs division which contains the proposed budget for 1991. Describes several of the areas within the tobacco industry that the budget will attempt to address and improve, such as environmental tobacco smoke (ETS), excise taxes and public smoking among others. Gives detailed backgrounds on each issue, identifies goals for that area and then analyzes different strategies to achieve those goals.